Assessment of Some Culture Media for Optimum Growth and Sporulation of Bipolaris sorokiniana Causing Spot Blotch of Wheat - Hijam, B.; Maharaja, G. L.; Roy, A.; Roy, V.; Hembram, S. (International Journal of Economic Plants, 2025)
An experiment was conducted during January–June, 2022 at Department of Plant Pathology, Uttar Banga Krishi Viswavidyalaya for the evaluation of the different culture media on the growth of the fungus Bipolaris sorokiniana causing spot blotch disease in wheat. Five different growth media, viz., Potato Dextrose Agar (PDA), wheat seed extract+PDA (WSPDA), wheat leaf decoction+PDA (WLPDA), carrot juice extract+PDA (CPDA), and oatmeal agar (OMA), were used in the experiment. PDA supplemented with different plant extracts exhibited differential growth and sporulation patterns on B. sorokiniana. The maximum colony diameter of 8.09 mm at 9 days after inoculation demonstrated that the OMA provided the best growth conditions. Moreover, based on the Tukey HSD test, the AUGPC of OMA was found to be the highest (34.68±1.3 cm2) and significantly different from all the other media used in the study. The OMA was followed by the WLPDA, which had an AUGPC of 22.6±1.79 cm2. The fungus sporulated in all the media considered for the present study, with OMA recording the highest sporulation with 44×104 spores ml-1, followed by WLPDA with 41×104 spores ml-1. The lowest level of sporulation was seen in CPDA, with a concentration of 15×103 spores ml-1. Based on the aforementioned results, it can be inferred that oatmeal agar was the most suitable medium for the development and sporulation of B. sorokiniana, followed by a mixture of wheat leaf decoction and PDA. On the other hand, PDA alone and carrot juice PDA were shown to be the least suitable media.